The Russia Corporate Governance Manual : Part V. Special Focus Section - International Finance Corporation; U.S. Department of Commerce (Washington, DC, 2013)
The Russia corporate governance manual has been divided into and is published in six parts: (i) corporate governance introduced; (ii) good board practices; (iii) shareholder rights; (iv) information disclosure and transparency; (v) special focus section; and (vi) annexes model corporate governance documents. The first four parts contain chapters that focus on core corporate governance issues, such as a company's board structure, information disclosure practices, and shareholder rights. Part five focuses on corporate governance issues of particular importance in the Russian context, namely corporate governance concerns during a company's reorganization, within holding structures, and relating to enforcement. Part six, finally, offers practical tools in the form of model documents, for example company codes, by-laws, and contracts. All issues are closely examined through Russian law and regulations; the Federal Commission for the Securities Market's Code of Corporate Conduct (FCSM Code) Code and, when applicable, internationally recognized best practices. This manual also provides government officials, lawyers, judges, investors, and others with a framework for assessing the level of corporate governance practices in Russian companies. Finally, it serves as a reference tool for the educational institutions that will train the next generation of Russian managers, investors, and policy makers on good corporate governance practices.